Prevalence and Risk Factors of Diabetes Mellitus Among the Inhabitants of Kumasi Metropolis - K, Agbogli H.; R, Annan; E, Agyeman-Duah; E, Mak-Mensah E. (Archives of Clinical and Biomedical Research, 2017)
In Ghana, there is an increasing prevalence of diabetes mellitus (DM) in the adult population, which stood at 3.35% by the end of 2013. About 8000 deaths were reported from diabetes in 2013. Changing dietary patterns and lifestyles are associated with the upsurge of DM and in Kumasi the prevalence is 9%. This work sought to determine DM prevalence and associated risk factors among adults in the Kumasi metropolis. The study involved 113 adults from the Oforikrom sub metro. Body Mass Index (BMI) were calculated from weight and height. Venous blood samples were collected for the determination of fasting blood glucose (FBG) using a spectrophotometer. Systolic and diastolic pressures were determined and socio-demographic data were collected using questionnaires. Mean age of participants was 41.8±1.3 years (females=44.9 and males=34.6, p<0.001), mean BMI was 27.3±0.6 kg/m2 (females=29.4 versus males=22.5 kg/m2, p<0.001) and mean FBG was 4.93±0.1 mmol/L (females= 4.97 versus males=4.84, p=0.55). Prevalence of hypoglycemia was 11.5%, normoglycaemia 74.3%, prediabetes 10.7% and diabetes was 3.5%. Close to 35% and 27% were obese and overweight respectively. More females were overweight or obese (82.3%) than the males (15%), p<0.001. Binary regression analysis showed gender as the only significant predictor of high FBG, with females having a 2.76 (95% CI 0.6, 12.7) increased odds of having high FBG compared to males. BMI, age, exercise, family history and diet were not significant predictors of FBG. In this population there was 3.5% observed prevalence of DM, similar to national prevalence, high prevalence of overweight and obesity, associated with female gender.